2009
DOI: 10.1021/ja905843e
|View full text |Cite
|
Sign up to set email alerts
|

Toolbox Approach to the Search for Effective Ligands for Catalytic Asymmetric Cr-Mediated Coupling Reactions

Abstract: Chromium catalysts derived from chiral sulfonamides represented by A effect the couplings of aldehydes with vinyl, allyl, or alkyl halides. With three distinct sites for structural modification, A affords access to a structurally diverse pool of chiral sulfonamides. The Cr catalysts derived from these sulfonamides exhibit a broad range of catalyst-substrate matching profiles. A strategy is presented to search for a satisfactory chiral sulfonamide for a given substrate. In order to demonstrate the generality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 48 publications
(13 reference statements)
1
55
0
2
Order By: Relevance
“…97 This work takes advantage of Fürstner’s 1996 report on the chromium-catalyzed Nozaki-Hiyama-Kishi reaction mediated by stoichiometric manganese metal, 98 along with chiral ligand XXVIII previously developed by Kishi. 99 One equivalent of ZrCp 2 Cl 2 , a highly mass-intensive reagent, and one equivalent of cesium iodide were required to improve catalyst turnover and reaction rate. Although good levels of anti -diastereo- and enantioselectivity were observed, the use of multiple stoichiometric metallic reagents and manganese metal diminish the appeal of this method, especially given the earlier disclosure of related alcohol-allene couplings that provide identical products with complete atom-efficiency.…”
Section: Acyclic Quaternary Carbon Stereocentersmentioning
confidence: 99%
“…97 This work takes advantage of Fürstner’s 1996 report on the chromium-catalyzed Nozaki-Hiyama-Kishi reaction mediated by stoichiometric manganese metal, 98 along with chiral ligand XXVIII previously developed by Kishi. 99 One equivalent of ZrCp 2 Cl 2 , a highly mass-intensive reagent, and one equivalent of cesium iodide were required to improve catalyst turnover and reaction rate. Although good levels of anti -diastereo- and enantioselectivity were observed, the use of multiple stoichiometric metallic reagents and manganese metal diminish the appeal of this method, especially given the earlier disclosure of related alcohol-allene couplings that provide identical products with complete atom-efficiency.…”
Section: Acyclic Quaternary Carbon Stereocentersmentioning
confidence: 99%
“…The DMP complexes with zinc (Zn-DMP), manganese (Mn-DMP), iron (Fe-DMP), cobalt (Co-DMP), nickel (Ni-DMP), copper (Cu-DMP), cadmium (Cd-DMP), mercury (Hg-DMP), and lead (Pb-DMP) were synthesized as described previously (Wang, 2009;Preston et al, 1968;Shen and Lush, 2010;Torbati et al, 2010;Das et al, 2013;Guo et al, 2009;Xia et al, 2011;Davies and Loose, 1976;Warad et al, 2011;Warad et al, 2013;Morsali et al, 2004;Hara et al, 2016) with some modifications, and identified by the element analysis.…”
Section: Synthesis Of Dmp Complexesmentioning
confidence: 99%
“…Since the first example of enantioselective allylation of aldehydes catalyzed by a Cr(II)–salen complex in 1999 by Cozzi and co-workers [12], several elegant catalytic enantioselective allylation and propargylation reactions have been developed by the groups of Nakada [1314], Berkessel [15], Kishi [16], Sigman [17], Yamamoto [18], Guiry [19], Chen [20], Gade [21], White [22], and Zhang [2325], respectively. The alkenylation and alkylation reactions were mainly explored by the Kishi group [2630], and they established a toolbox approach to search for the specific ligand with a given substrate in the Cr-catalyzed process [28]. They successfully applied the method to the natural product total synthesis like halichondrin B and norhalichondrin B, and in the subsequent pharmaceutical study, finally leading to the discovery of the anticancer drug Eribulin [3135].…”
Section: Introductionmentioning
confidence: 99%